3D seismic velocity models from local earthquake tomography furnish new insights on the Mount Etna volcano (Southern Italy) - C. Totaro; M. Aloisi; C. Ferlito; B. Orecchio; D. Presti; S. Scolaro (Scientific Reports)
Abstract We present a new seismotomography investigation providing a 3-D overall model of Vp, Vs and Vp/Vs for Mt. Etna, the largest and most active volcano in Europe. We estimated and jointly evaluated P- and S-wave velocity patterns together with the Vp/Vs ratio, particularly useful to discriminate the presence of groundwater, gas, and melts and thus very precious for volcano investigations. We applied the LOTOS software to ~ 4600 crustal earthquakes that occurred in the Etnean area during the last 26 years, the longest time-interval ever analysed for Mt. Etna. This wide dataset has allowed us to characterize the volcano velocity structure getting over possible singularities due to specific eruptive phases. Our results further refined the high velocity body widely recognized in the south-eastern sector of Mt. Etna by furnishing new clues on the possible former magma pathways. Moreover, the obtained 3D seismic velocity model depicted new anomalies revealing the presence of: (i) two shallow underground aquifers in the northern Etnean sector; (ii) a volume of strongly fractured rocks filled of fluids along the eastern flank; (iii) a quite deep region of probable fluid accumulation apparently not linked to the volcanic activity in the western sector.